Challenge Based Learning for the development of digital skills in students of an Institute of Ica - Romani-Pillpe, Guillermo (2022)
The purpose of this work was to determine the influence of challenge-based learning for the development of digital skills in students of an Ica institute. To achieve the objective, the following methodology was obtained: experimental type, quantitative approach and pre-experimental design. In this regard, it should be said that a program was used, developed in 16 sessions. We worked with a sample of 21 students in the Technological Research and Innovation course. For the objective evaluation, the rubric instrument was applied —pretest and posttest—; the observation technique allowed the variable to be measured. Likewise, the data was processed using the static SPSS v.26, which was explained through illustrations —tables and figures—. The statistical results of Wilcoxon show values ​​to accept the H1 raised in the investigation. The study concluded that there is an influence on the development of digital skills in students of an Ica institute.